What Do Filipino Gay Male College Students Want to Learn in Sex Education? - Manalastas, Eric Julian; Macapagal, Raymond Aquino (Review of Women's Studies; Vol 15 No 1 (2005): Review of Women's Studies Volume XV, Number 1 (January-June 2005))
Using a learner-centered, mixed qualitative-quantitative approach, we explored the needs, experiences, and contexts of sexuality education of Filipino gay and bisexual male college students. A convenience sample of 121 self-identified gay/bisexual male Filipino college students answered a structured questionnaire asking them to rate 44 possible topics they would like to be discussed in a classroom-based college human sexuality class. Topics most wanted by gay/bisexual learners were sexual identity and orientation, love, body image, HIV/AIDS, gender roles, and friendship. Survey findings are grounded in the context of learners' experiences of sexuality education which we explored using a focus group with seven selected Filipino gay students. Two hundred nineteen (219) suggestions made by respondents for improving sexuality education are also analyzed and presented as well as recommendations for further research.